In Silico Prediction of selected major Phytochemical constituents of Chandraprabha Vati as CYP 2C9 Inhibitor - Sivaguru Paramesh Ahalya; Thangavel Mahalingam Vijayakumar; Rajappan Chandra Satish Kumar (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: Computational docking is a crucial technique for developing better novel drugs. The behaviour of a test molecule in the coupling site of the desired receptor target can be described using a docking method. In recent years world’s population relies mainly on natural and herbal based marketed formulation for health care. In this study components of the main ingredients Shilajit and Shudha guggulu in the preparation of Chandraprabha Vati is evaluated for the binding affinity towards CYP2C9. It is done by using a comparator drug Glimepiride since it is metabolises using CYP2C9. Purpose: There is an increase in usage of ayurvedic drugs as an add-on or supplement along with the therapeutic drug plan.purpose of this study is to know the interaction potential of the components of the Herbal formulation. Study Design: In Silico Study. Materials and methods: Online tools and Database such as Protein data bank, IMPPAT, Pubchem, pkCSM, CB-Doc were used for choosing of protein, Docking, ADMET prediction, Drug-likeness of the components. Results and Discussion: The vina score of the Phytochemical constituents of Chandraprabha Vati was observed, many exhibit good binding effect. It demonstrates the Binding affinity of the phytochemicals with the target. Conclusion: This current study concludes that Episesamin, Stigmasterol, Thunbergene, E- Guggulusterone, Cholesterol, beta-sitosterol, Mukulol, Isorhamnetin, 16alpha-Hydroxyprogesterone have Good Binding affinity to the Target as well as predicted to have CYP2C9 inhibition property.